Immunity in Protochordates: The Tunicate Perspective - Franchi, Nicola; Ballarin, Loriano (Frontiers in Immunology, 2017)
Tunicates are the closest relatives of vertebrates and their peculiar phylogenetic position explains the increasing interest towards tunicate immunobiology. They are filter-feeding organisms and this greatly influences their defense strategies. The majority of the studies on tunicate immunity were carried out in ascidians. The tunic acts as a first barrier against pathogens and parasites. In addition, the oral siphon and the pharynx represent two major, highly vascularized, immune organs, where circulating hemocytes can sense nonself material and trigger immune responses that, usually, leads to inflammation and phagocytosis. Inflammation involves the recruitment of circulating cytotoxic, phenoloxidase (PO)-containing cells in the infected area, where they degranulate as a consequence of nonself recognition and release cytokines, complement factors and the enzyme PO. The latter, acting on polyphenol substrata, produces cytotoxic quinones, that polymerize to melanin, and reactive oxygen species, that and induce oxidative stress. Both the alternative and the lectin pathways of complement activation converge to activate C3: C3a and C3b are involved in the recruitment of hemocytes and in the opsonization of foreign materials, respectively. The interaction of circulating professional phagocytes with potentially pathogenic foreign material can be direct or mediated by opsonins, either complement-dependent or complement-independent. Together with cytotoxic cells, phagocytes are active in the encapsulation of large materials. Cells involved in immune responses, collectively called immunocytes, represent a large fraction of hemocytes and the presence of a cross-talk between cytotoxic cells and phagocytes, mediated by secreted humoral factors, was reported. Lectins play a pivotal role as pattern-recognition receptors and opsonizing agents. In addition, variable region-containing chitin-binding proteins, identified in the solitary ascidian Ciona intestinalis, control the settlement and colonization of bacteria in the gut.